Construction and Validation of a Novel Pyroptosis-Related Gene Signature to Predict the Prognosis of Uveal Melanoma - Cao, Yuan; Xie, Jiaheng; Chen, Liang; Hu, Yiming; Zhai, Leili; Yuan, Jin; Suo, Long; Shen, Yaming; Ye, Rong; Li, Jiajun; Gong, Zixuan; Dong, Yunfan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Uveal melanoma is the most common primary intraocular tumor with a poor prognosis. Currently, treatment for UVM is limited, and the development of drug resistance and tumor recurrence are common. Therefore, it is important to identify new prognostic biomarkers of UVM and explore their role in the tumor microenvironment. Pyroptosis is a way of cell programmed death, and related research is in full throttle. However, the role of pyroptosis in UVM is unclear. In this study, we constructed the prognosis model of pyroptosis-related genes of UVM. This model can accurately guide the prognosis of UVM, and different groups differ in immune infiltration. We further verified our results in cell experiments. To some extent, our study can provide new ideas for the diagnosis and treatment of UVM.